Investigating links between the immune response and Helicobacter pylori-mediated disease outcomes - Alzahrani, Shatha (2024)
Background: Helicobacter pylori is the primary cause of chronic gastritis and peptic ulcer disease and a significant risk factor for gastric adenocarcinoma. Numerous studies have reported the role of cytokines in the pathogenesis of gastric inflammation during H. pylori infection and disease outcomes are more likely with virulent strains that carry the Cytotoxin Associated Gene Pathogenicity Island (cag PAI). Interleukin-16 (IL-16) is a multifunctional cytokine implicated in various chronic inflammatory conditions, such as inflammatory bowel disease, asthma, and rheumatoid arthritis. Elevated IL-16 levels have previously been observed in the serum of gastric cancer patients compared to healthy controls. However, the connection between IL-16 production and H. pylori infection remained unclear. A comprehensive study profiling plasma cytokine levels across different stages of gastric cancer prognosis, including non-atrophic gastritis, atrophic gastritis, intestinal metaplasia, and gastric cancer could provide insights into the correlation between cytokines and disease progression and their potential as biomarkers for gastric cancer. Previous research demonstrated H. pylori's ability to induce IL-16 production in gastric epithelial cell lines. Since monocytes and dendritic cells are among the first cells to encounter H. pylori after it breaches the gastric epithelial barrier, the effect of H. pylori and its virulence factors on IL-16 production in these cells has not been explored.